Effectiveness of the BTI (Bogor Traffic Info) Application in Supporting SIM Service Units in the Jurisdiction of the Bogor City Police - Harmada, Satria Ramadhani Kusuma (Police Studies Review, 2024)
Bogor City is a region with a high population density with high potential for motor vehicle ownership, this indirectly affects the traffic conditions in the region. With this situation and condition, it is necessary to have innovations that can support the performance of Bogor City Police in the field of traffic management. Bogor Traffic Info (BTI) is one form of innovation in the form of an application initiated by the Bogor City Police in order to support improved services to the public in the field of traffic management. However, to assess the success of the application of an innovative product, an evaluation of the effectiveness of the innovation product is needed. The effectiveness of the application of the BTI application in the Police jurisdiction of Bogor city is further examined using a qualitative approach with data collection techniques in the form of document studies, observations and interviews with four research variables namely a general description of the research objects (Bogor City, Bogor City Police and BTI applications), community responses and the applicant for an extension of the driving license (SIM) to the BTI application, the effect of the application of the BTI application to the phenomenon of violations of the SIM code of conduct in driving and the final factor are aspects that affect the user of the BTI application to do the SIM extension. Based on the analysis of the four factors, it can be concluded that the application of the Bogor Traffic Info (BTI) application has not been effective in supporting improved services to the public in the field of traffic management in areas that are the responsibility of the Bogor City Police.